Dodging the Draft (Tax): How China's Draft Inheritance Tax Law Turns a Blind Eye to the Rich, a Good Eye to the Masses, and How a Reorientation Can Be Realized - Justin T. Brown (Washington University Global Studies Law Review, 2013)
This Note will examine the 2004 Draft Inheritance Tax Law and provide suggestions for improving the law. Part II provides a background of the social and political context leading up to the Draft Law and of the developments since 2004. Part III examines the Draft Law itself and comments on its shortcomings, omissions, and areas needing improvement. Finally, Part IV summarizes the arguments for and against the tax examined in Part III and concludes that a wealth transfer tax could be a useful tool to achieve China’s numerous social objectives. The Draft Law of 2004, however, requires many serious revisions before implementation.
Keywords: tax law; China; draft inheritance tax; 2004 Draft Inheritance Tax Law